2017
DOI: 10.1111/cpr.12370
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation inhibition of cisplatin‐resistant ovarian cancer cells using drugs screened by integrating a metabolic model and transcriptomic data

Abstract: The proposed strategy was successful to identify drugs effective on the viability of resistant cancer cells. This strategy can enhance the potency of treatments for drug-resistant cancer cells and provides the possibility of using existing drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…To our knowledge, this is the first study that combines proteomics data with this type of computational analyses to study drug’s mechanism of actions in breast cancer. However, FBA was successfully used in ovarian cancer cells to propose new therapeutic targets and to study the effect of drugs targeting metabolism and their synergies [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study that combines proteomics data with this type of computational analyses to study drug’s mechanism of actions in breast cancer. However, FBA was successfully used in ovarian cancer cells to propose new therapeutic targets and to study the effect of drugs targeting metabolism and their synergies [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the past decade, various algorithms for integration of omics data and metabolic models have been developed to predict the anti‐tumor effect of non‐oncological drugs . The algorithm of transcriptional regulated flux balance analysis aimed to construct cancer cell‐specific models has successfully identified terbinafine as a potential anti‐tumor drug . Existing evidence suggests that terbinafine suppresses the proliferation of colon cancer cell line by the involvement of the p53‐associated signaling pathway .…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that terbinafine, which is commonly used for the treatment of superficial mycosis, might have an anti‐tumor effect. An in silico analysis by integrating a generic human metabolic model with transcriptomic data found that terbinafine can inhibit the proliferation of resistant cancer cells while minimally affecting normal cells . Experimental data has shown that terbinafine can decrease the proliferation in various cultured human malignant cells with a dose‐dependent effect .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, there is still a lack of mature and convincing theory on specific and precise cellular molecular mechanisms of the initiation and development of HCC. 5 Decrypting the underlying molecular mechanisms of cell biology will shed light on the complex molecular and cellular pathways that mediate the initiation and progression of HCC. In addition, it will provide a potential treatment strategy against HCC.…”
Section: Introductionmentioning
confidence: 99%